Forma y prueba de los contratos mercantiles - Zegarra Mulánovich, Alvaro (Revista de Derecho, 2019)
This paper analyzes the scope of the general rules on the form of contracts and other legal acts, as well as the evidentary rules contained in the Peruvian Commercial Code, contrasting them, if the case be, whith the provisions of general private law.